Impact of Immigration Policies on Migrant Integration in Azerbaijan - Yusifli, Sujaddin; Hamidova, Rahila; Baghirli, Murad (ADA University, 2025)
This paper critically assesses how Azerbaijan’s migration governance has shifted from a quota-based, control-oriented regime to one that is beginning to recognise integration as a policy imperative, and it does so through a qualitative, exploratory design grounded in thematic analysis of five in-depth interviews with recent migrants, a comprehensive literature and policy review, and a three-option policy evaluation framework. After tracing the post-independence evolution of legislation—culminating in the 2013 Migration Code and the establishment of the State Migration Service—the study identifies persistent gaps: frequent permit renewals, language barriers, limited recognition of foreign credentials and unequal access to public services. Applying criteria of effectiveness, efficiency, equity, feasibility and flexibility, the analysis finds that “Targeted Integration Measures” (Alternative 2)—notably free Azerbaijani‐language and civic-orientation courses, one-stop advisory centres and strengthened institutional coordination—strike the most pragmatic balance between ambition and political-administrative realism at the country’s current stage. The paper concludes that implementing these incremental programmes, combined with systematic monitoring and partnerships with international organisations, will yield quick wins in migrant well-being and labour-market productivity while laying empirical and institutional groundwork for more far-reaching legal reforms in the medium term; in short, it argues that smart, phased integration policy is essential for Azerbaijan to harness migration as a driver of sustainable economic growth and social cohesion.
Keywords: Emigration and immigration -- Government policy -- Azerbaijan; Immigrants -- Services for -- Azerbaijan; Migrant labor -- Government policy; Integration -- Government policy -- Azerbaijan; Public and International Affairs